Implementation of High Dose-rate Brachytherapy for Cervix Cancer in a Low-income Country - Nurkic, Sommer R. (Ann Glob Health, 2018)
BACKGROUND: The purpose of this study is to detail the implementation of HDR brachytherapy at the only radiotherapy center in Nicaragua. METHODS: Patients are treated with external-beam radiotherapy to 46–50Gy at 2Gy/fraction to the pelvis. A gynecologic examination is performed weekly. Once the cervical os is visualized, brachytherapy is initiated. HDR is delivered in four fractions of 7Gy twice weekly. HDR occurs in two phases: preparation and delivery. Treatment preparation occurs in the procedure room, which includes anesthization, cervical dilation, and brachytherapy applicator placement using fixed-geometry tandem and ring with a rectal blade. The applicator is immobilized and the patient transferred to a stretcher and transported to the treatment delivery room. HDR is performed with the patient on the stretcher to minimize motion. AP and lateral films are taken using portable equipment. Physics staff digitize Point A, rectal point, and bladder point. A standard plan is loaded and approved prescribing 7Gy to Point A. If dose to the rectal or bladder points exceeds the constraint, the applicator is adjusted or vaginal packing is added and films repeated. RESULTS: Nearly 10 years after implementing the HDR program, the center is treating 11–15 women with HDR brachytherapy for cervix cancer daily. Because the procedure is carried out over two separate rooms, patients can be staggered and more treated daily. The rooms turn over every 45 minutes. CONCLUSIONS: HDR brachytherapy for cervix cancer has been successfully established in Nicaragua. Significant challenges remain, and there is a role for developed countries to collaborate.